Wild pepper species consumed as green leafy vegetables among Orang Ulu groups in Asap-Koyan Belaga, Sarawak - Alan, Ribka; Saupi, Noorasmah; Tunung, R.; Lepun, Philip (Rynnye Lyan Resources, 2022)
Wild pepper plants are a valuable food source, particularly to the Sarawak local community living in rural areas. However, these plants remain unknown to the public due to the lack of scientific information disseminated to the public, and there is a rapid decline in traditional knowledge on edible plants from natural resources. The documentation and evaluation of traditional knowledge related to the diversity and usage of wild pepper plants are crucial. Therefore, this study was aimed to document and evaluate the species from Piperaceae vegetables as a food source among the Orang Ulu community in Belaga, Sarawak. Face-to-face interviews involving thirty respondents from Sungai Asap-Koyan, Belaga, Sarawak were conducted. This was to gather information on the diversity, distribution, usage, consumption and perception of wild pepper plants. From the results, wild peppers species commonly consumed were Piper umbellatum, P. borneense, P. auritifolium and P. rueckeri. Among the species, P. borneense var 1 and P. umbellatum showed significant distribution in the area. The consumption of wild pepper as leafy vegetables is common among the community as they prefer the taste, aroma, and due to their belief in its nutritional values and medicinal properties. The plant is also used as an additive in cooking, and it is widely accepted among the community. It has the potential to be commercialized and introduced as a food crop. Future studies should be conducted to assess and apply ethnic knowledge for improved performance of Piper species consumption among larger communities.